Syndesmotic Fixation Utilizing a Novel Screw: A Retrospective Case Series Reporting Early Clinical and Radiographic Outcomes. Issue 5 (October 2020) - Stenquist, Derek; Velasco, Brian T.; Cronin, Patrick K.; Briceño, Jorge; Miller, Christopher P.; Riedel, Matthew D.; Kwon, John Y.
Background. Syndesmotic disruption occurs in 20% of ankle fractures and requires anatomical reduction and stabilization to maximize outcomes. Although screw breakage is often asymptomatic, the breakage location can be unpredictable and result in painful bony erosion. The purpose of this investigation is to report early clinical and radiographic outcomes of patients who underwent syndesmotic fixation using a novel metal screw designed with a controlled break point. Methods. We performed a retrospective review of all patients who underwent syndesmotic fixation utilizing the R3lease Tissue Stabilization System (Paragon 28, Denver, CO) over a 12-month period. Demographic and screw-specific data were obtained. Postoperative radiographs were reviewed, and radiographic parameters were measured. Screw loosening or breakage was documented. Results. 18 patients (24 screws) met inclusion criteria. The mean follow-up was 11.7 months (range = 6.0-14.7 months). 5/24 screws (21%) fractured at the break point. No screw fractured at another location, nor did any fracture prior to resumption of weight bearing; 19 screws did not fracture, with 8/19 intact screws (42.1%) demonstrating loosening. There was no evidence of syndesmotic diastasis or mortise malalignment on final follow-up. No screws required removal during the study period. Conclusion. This study provides the first clinical data on a novel screw introduced specifically for syndesmotic fixation. At short-term follow up, there were no complications and the R3lease screw provided adequate fixation to allow healing and prevent diastasis. Although initial results are favorable, longer-term follow-up with data on cost comparisons and rates of hardware removal are needed to determine cost-effectiveness relative to similar implants. Level of Evidence : Level IV: Retrospective case series